Pengaruh Besar Sudut Kampuh V Terhadap Von Mises Stress Material Pada Proses Pengelasan Berbasis Metode Elemen Hingga - Zulvikar, Zulvikar; Kadir, Abd; Samhuddin, Samhuddin (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
Welding is one of the joining technologies that has experienced significant developments from time to time, both from the type of welding equipment to the joining method used. This study aims to determine the effect of the large angle of V on Von Mises stress material in the welding process based on the finite element method. The tool used to model Equivalent von misses stress and Equivalent Elastic Strain with the help of finite element method software, the material used is AISI 4130. From the simulation results, it shows that the largest Equivalent von misses stress is found at the 45° V seam angle, which is 1.7251x108 Pa, while the lowest equivalent von misses stress is found at the angle of V 60°, which is 1.7162x108 Pa. As for the Equivalent Elastic Strain, the largest is found at the large V 30° joint angle, which is 0.00129 m or 1.29 mm, while the lowest strain value is found at the 45° joint angle of 0.0011564 m or 1.15 mm. Keywords: Equivalent von misses stress, Equivalent elastic Strain, Large angle of V, Finite element method